2021
DOI: 10.7498/aps.70.20210482
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of structure and superconducting properties of low-temperature phase of Pb-Bi alloy films

Abstract: Lead-bismuth (Pb-Bi) alloys, as a superconducting material, have been widely studied at their superconducting transition temperatures and the critical magnetic fields for different composition ratios. Most of experimental studies focused on the stable ε phase formed at high temperatures, but less on the Pb-Bi alloys grown at low temperatures. So far, the structural and superconducting properties of the low-temperature Pb-Bi phases are far from good understanding. Here, we report our investigation of structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
1
2
0
1
Order By: Relevance
“…15,41,44 The growth morphology is clearly contrasted from the formation of Pb−Bi alloy films through the codeposition of Pb and Bi. 46,47 This clearly indicates that the extra islands are Bi islands in a distinct monolayer structure from that of the α-Bi films reported previously.…”
Section: Square-lattice Bismuth Monolayer On Pb Filmssupporting
confidence: 59%
See 1 more Smart Citation
“…15,41,44 The growth morphology is clearly contrasted from the formation of Pb−Bi alloy films through the codeposition of Pb and Bi. 46,47 This clearly indicates that the extra islands are Bi islands in a distinct monolayer structure from that of the α-Bi films reported previously.…”
Section: Square-lattice Bismuth Monolayer On Pb Filmssupporting
confidence: 59%
“…The height profile of one representative island is shown in Figure d, where one can measure the diameter of the 1 ML (2 ML) island as 16 nm (3 nm) and the layer height as ∼3.2 Å for both layers. The monolayer height is distinct from that of Pb islands and half of those of most α-Bi films reported, which correspond to the puckered structure. ,, The growth morphology is clearly contrasted from the formation of Pb–Bi alloy films through the codeposition of Pb and Bi. , This clearly indicates that the extra islands are Bi islands in a distinct monolayer structure from that of the α-Bi films reported previously.…”
Section: Resultsmentioning
confidence: 58%
“…不同元素配比的铅铋(Pb-Bi)合金相的超导 转变温度和临界磁场性质都被大量研究 [14−16] , 包 括合金相图中的稳定e相, 即Pb 7 Bi 3 [17] . 通常情 况下, 低温制备的铅铋合金结构不同于e相 [18,19] , 但其具体的结构信息和电子学性质仍缺乏深入 研究. 我们之前的工作报道了低温稳定的Pb 1-x Bi x (x ≈ 0.1)合金相 [20] , 确定了合金结构是部分铅被 dI/dV谱超导能隙的拟合采用如下公式 [21] :…”
Section: 引 言unclassified
“…Recently it was found that PbBi compound of atomic thickness grown on silicon surface was found to demonstrate one-dimensional metallic spin-polarized electron states (Mihalyuk et al, 2021) a promising quantum effect relevant for spintronic applications. Remarkably that Pb-Bi films with a nominal thickness of about 4.8 nm grown on silicon demonstrate a superconducting transition at 6.13 K (Tian et al, 2021;Wang et al, 2022). In this regard there is an interest for engineering Pb and Bi containing materials on other semiconducting surfaces.…”
Section: Introductionmentioning
confidence: 99%